Distribution Characteristics of Soil Particles and Their Relationships With Soil Organic Carbon Components in the Alluvial/Sedimentary Zone in the Lower Reaches of the Yellow River - Zhang, Junhua; Li, Guodong; Ding, Shengyan; Tian, Huiwen; Ren, Xiaojuan; Liu, Man; Zheng, Yaping (Frontiers in Environmental Science, 2022)
Land use and sediment alluviation/deposition are the main factors influencing the vertical distributions of particles with different sizes and the soil organic carbon (SOC) form. Based on field investigation, experimental analysis and data analysis, soil particle characteristics and the relationships with SOC compositions are studied in the typical alluviation/deposition area of Kaifeng-Zhoukou. In soil profile, the particulate matter is mainly 10-50 μm and 50-250 μm in size with an average content of approximately 65%, the content difference within the same size particle range is small. There is a large content range of the <1000 μm particles, which is the main factor affecting the change in soil properties. The fractal dimension (D) of soil particles ranges from 2.21 to 2.78. The value of D of each layer in farmland is higher than that of each layer in woodland, and it has been observed that DNF(farmland in the nonflooded area) > DF(farmland in the flooded area) and DNW(woodland in the nonflooded area) > DW(farmland in the nonflooded area). The contents of particles smaller than 50 μm have a positive effect on D, and the particles exceeding 50 μm have a negative effect. The contents of the 10-50 μm, <2 μm, 2-5 μm and 5-10 μm particles and their dynamic variances are the root causes of the D differences in the farmland/woodland soil in the FA and NFA. SOC components combine to a greater extent with silt and clay that are <10 μm in size in the NF, and the stability is relatively high. The contents of the 10-50 μm and <10 μm particles are the main reasons for the differences in the soil active and nonactive organic carbon contents in the FA and NFA. The difference in D can reflect the change in SOC and its components and can be used as an index to characterize the variance in soil properties and quality. This study revealed the influences of the different particle sizes on the SOC components, which will expand and enrich the current area of study and further provide a basis to increase SOC and improve soil quality.